Mode of delivery and outcome of patients with a previous scar at Charlotte Maxeke Johannesburg Academic Hospital - Mokaya, Momanyi (My University, 2017)
The setting of this study was at the Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) a tertiary referral and teaching hospital attached to the University of Witwatersrand situated in Parktown, Johannesburg. The hospital manages all high risk pregnancy including previous caesarean sections. This study evaluated women with one previous scar at CMJAH for their: antenatal choice of delivery method, eventual delivery method and pregnancy outcome. Over the years there has been a significant uptrend of caesarean sections and consequently also an increasing number of women with one previous scar with subsequent pregnancies. Objectives: 1) To obtain the indication for the mothers’ first caesarean section, 2) To determine the mothers’ choice of delivery method following their first caesarean section, 3) To determine the actual mode of delivery and factors that influenced it, 4) To establish short term neonatal outcome following delivery, 5) To establish short term maternal outcome following delivery. Methodology: The study was a prospective cohort study of women with one previous scar who attended the antenatal clinic at the Charlotte Maxeke Johannesburg Academic Hospital (CMJAH). The aim was to compare their antenatal choice of delivery to how they eventually delivered. 100 women were recruited from the antenatal clinic from 1st July 2016 to 30th September 2016. Data was collected via interviewing the mothers and also from hospital records; this was captured on a data sheet. Data was then analysed using STATA software. Results: One hundred women were followed up to delivery. 63 wanted to deliver via vaginal birth after caesarean section (VBAC) during their antenatal period, 35 wanted a repeat caesarean section and two were still undecided on their preferred mode of delivery. 22 women eventually managed to have VBAC (including 4 assisted deliveries). There were a total of 78 deliveries via caesarean section 46 being emergency caesarean sections and 32 being elective caesarean sections. The attempted VBAC success rate was 35% (including assisted deliveries) the remainder receiving emergency caesarean sections. Of the patients who wanted repeat caesarean section, 94.3% delivered by caesarean section. 76% of babies had no adverse short term outcome while 87% of mothers had no short term complications post-delivery. There was statistically no difference between short term complications of mother and foetus in both modes of delivery. VI Conclusion: Women who choose caesarean section delivery during their antenatal period are much more likely to deliver via their preferred mode compared to women who choose VBAC as their mode of delivery, statistically significant, P<0.001.The main reasons for conversion of a VBAC to caesarean section observed were foetal distress and poor progress. Overall outcomes of mother and foetus were not statistically significant between vaginal and caesarean section delivery routes, though the most severe maternal complications were observed in emergency caesarean section deliveries.
Research report submitted to the University of the Witwatersrand in partial fulfilment for the degree of Masters of Medicine (Obstetrics and Gynaecology)
Keywords: Cesarean section; Anesthesia